Assessment of phosphorus fertilizer practices in altered wetland soils using uncertainty analysis. (5th March 2013) - Litaor, M. I; Chashmonai, I.; Barnea, I.; Reichmann, O.; Shenker, M.
Abstract: Intensive P fertilizer application is widely practised in East Mediterranean altered wetland soils, even when results from the Olsen‐P extract indicate sufficiency (>10 mg P/kg). To reduce or even eliminate this practice we conducted a large field study to test the feasibility of a major reduction in the use of P fertilizers. A total of 90 sample sites were evenly spaced with respect to their parent material (deep peat, shallow peat, marl). Soils were analysed for Olsen‐P, bulk density, pH, electrical conductivity, and nitrate, chloride and sulphate in saturated paste extracts. We determined variograms and estimated the spatial structure of Olsen‐P data by ordinary kriging. We then used a sequential Gaussian model to produce 100 alternative simulations to measure the joint spatial uncertainty of P concentrations in the study area (ca. 1500 ha). Finally, we post‐processed the simulation results to compute the probability of exceeding the threshold Olsen‐P value of 10 mg/kg. The simulation results indicate a high probability of exceeding the 10 mg/kg threshold in most peat soils supporting an earlier recommendation to reduce or even eliminate P fertilizer application in these fields. On the other hand, a very low probability of exceeding this threshold was observed in most marl soils justifying continued fertilizer application. However, the added P is likely to affect adjacent waterways and increase potential downstream eutrophication due to high conductance and flow continuity between the marl soils and adjacent waterways.